Factors of Innovative Development of Digital Economy in Uzbekistan - Boriboev Erkinjon Norboy ugli (European Science Publishing, 2023)
In this article, the factors of the development of the digital economy in our republic, especially the innovative factors, are studied. By implementing the digital economy program in the Republic of Uzbekistan, the main results, i.e., the creation of a new regulatory and legal framework, the legal obstacles that prevent the creation of new technologies, and the creation of the infrastructure of the digital economy and development, including the development of networks, data processing centers, technical and software in accordance with the requirements of the times, ensuring the comprehensive development and renewal of the education system, creating a thorough basis for the development of various companies, firms, state enterprises and small businesses in the country, and the digital economy It is analyzed how to achieve the creation of many organizations in the field.
Keywords: digital economy, innovation, strategy, technology, e-business.